Systematic Literature Review: Islamic Wealth Management Perspective - Muhammad Fatchullah El Islami; Hoirul Anam; Nasrudin; Jakfar Shodiq (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2025)
Purpose – Islamic Wealth Management is a concept and teaching that helps individuals or groups manage assets in an Islamic manner. The fundamental difference between conventional and Islamic asset management lies in the limitations of acquiring, saving and spending in the halal sector. However, practically many people still ignore the importance of Islamic management. This study aims to reveal how to manage assets with the Islamic Wealth Management method. Design/Methods/Approach – This research uses a qualitative approach to Systematic Literature Review. The research data comes from a literature study of published journal articles in 2014-2023 with the help of Harzing Publish or Perish 8 software. Findings – The research results from 21 journal articles following the criteria show that asset management in the IWM concept is still limited in meeting primary needs. Many people ignore asset management in the aspects of wealth protection and wealth distribution. The use of Islamic financial institutions is still lacking, and many do not prioritize the distribution of wealth to religious interests. Research Implications/Limitations – The IWM concept provides a solution that Islamic wealth must be obtained from halal places, stored halal, spent on halal objects, as needed, and not wasteful by paying attention to the importance of 5 aspects of IWM, namely Wealth Creation, Wealth Accumulation, Wealth Protection, Wealth Spending, and Wealth Distribution. Allah guides his servants who have wealth to be used for the benefit of the world and the hereafter.